The world predictive power of U.S. equity market skewness risk - CHEN, Jian (Institutional Knowledge at Singapore Management University, 2019)
This study investigates the cross-country impact of U.S. equity market skewness risk. We find that a large decrease in the U.S. market skewness significantly predicts higher future returns on international equity markets. The predictability remains significant after controlling for a set of U.S. and local forecasting variables. Furthermore, we find strong predictability in- an out-of-sample setting and the predictability delivers a large economic value. The U.S. market skewness also forecasts U.S. economic recessions and international market conditions, consistent with the international three-moment capital asset pricing model (three-moment CAPM) and the intertemporal capital asset pricing model (ICAPM).